Anti-reflux mucosectomy for refractory gastroesophageal reflux disease: a systematic review and meta-analysis - Garg, Rajat; Mohammed, Abdul; Singh, Amandeep; Schleicher, Mary; Thota, Prashanthi N.; Rustagi, Tarun; Sanaka, Madhusudhan R (Endoscopy International Open, 2022)
Background and study aims Anti-reflux mucosectomy (ARMS) is an emerging endoscopic treatment for refractory gastroesophageal reflux disease (GERD). We conducted a systematic review and meta-analysis to evaluate the safety and efficacy ARMS in refractory GERD.Methods A comprehensive search of multiple databases (through March 2020) was performed to identify studies that reported outcomes of ARMS for refractory GERD. Outcomes assessed included technical success, clinical response, and adverse events (AEs). Clinical response was defined as discontinuation (complete) or reduction (partial) of proton pump inhibitors post-ARMS at follow up.Results A total of 307 patients (mean age 46.9 [8.1] years, 41.5 % females) were included from 10 studies. The technical success and clinical response rates were 97.7 % (95 % confidence interval [CI], 94.6–99.0) and 80.1 % (95 % CI, 61.6–91.0), respectively. The pooled rate of complete and partial clinical response was 65.3 % (95 % CI, 51.4–77.0) and 21.5 % (95 % CI, 14.2–31.2), respectively. The rate of AEs was 17.2 % (95 % CI, 13.1–22.2) with most common AE being dysphagia/esophageal stricture followed by bleeding with rates of 11.4 % and 5.0 %, respectively. GERD health-related quality of life (GERD-HRQL) (mean difference [MD] = 14.9, P < 0.001), GERD questionnaire (GERD-Q) (MD = 4.85, P < 0.001) and mean acid exposure time (MD = 2.39, P = 0.01) decreased significantly post-ARMS as compared to pre-procedure. There was no difference in terms of clinical response and AEs between ARMS and ARMS with banding on subgroup analysis.Conclusions ARMS is a safe and effective procedure for treatment of refractory GERD with high rates of clinical response, acceptable safety profile and significant improvement in GERD-related quality of life. Prospective studies are needed to validate our findings.